Pengaruh Lingkungan Kerja dan Komunikasi Interpersonal Terhadap Kinerja Guru dan Pegawai dengan Gaya Kepemimpinan Sebagai Variable Moderating pada SMAN 2 Bukittinggi - Rika Devia; Almasdi Almasdi (STIE AMKOP, 2023)
This study aims to determine and analyze the influence of Work Environment on Teachers and Employees Performance, the influence of Interpersonal Communication on Teacher and Employees Performance, the influence of Leadership Styles modereates the effecy of Work Environment and Interpersonal Communication On Teacher and Employees Performance at SMA Negeri 2 Bukittinggi. The population in this study amounted to 74 teachers and employees who served at SMA Negeri 2 Bukittinggi. Data collection techniques in this study by distributing questionnaires, interviews and observations. The data is processed using the SmartPLS 4.0 application. The results of the analysis can be concluded that: (1) Work Environment has a positive and significant influence on Teacher and employees Performance at SMA Negeri 2 Bukittinggi, (2) Interpersonal Communication has a positive and significant influence on Teacher and Employees Performance at SMA Negeri 2 Bukittinggi (3) Leadership Style is positively moderates the effect of Work Environment on Teacher and Employees Performance at SMA Negeri 2 Bukittinggi, and (4) Leadership Style positively moderates the effect of Interpersonal Communication on Teacher and Employees Performance at SMA Negeri 2 Bukittinggi. Keywords: Work Environment, Interpersonal Communication, Teacher, Employees Performance, Leadership Style